The influence of physical fitness, nutritional status, and sports participation on physical education learning outcomes among students - Windi Ilham; Yanuar Kiram; Gusril Gusril; Ahmad Chaeroni (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study aimed to analyze the direct and indirect effects of physical fitness, nutritional status, and sports participation on learning outcomes in Physical Education, Sports, and Health among elementary school students in Padang City. This study employed a quantitative design using path analysis. The sample consisted of 67 fifth-grade elementary school students selected through purposive sampling. Physical fitness was measured using the Modified Harvard Step Test, nutritional status was assessed through Body Mass Index, sports participation was measured using a 60-item questionnaire, and learning outcomes were obtained from students’ Physical Education, Sports, and Health scores. Data were analyzed using descriptive statistics and path analysis with SPSS. The findings showed that physical fitness (β = 0.121; p = 0.019), nutritional status (β = 0.249; p = 0.007), and sports participation (β = 0.518; p < 0.001) significantly affected learning outcomes. Sports participation demonstrated the strongest contribution and also mediated the effects of physical fitness and nutritional status on learning outcomes. Physical fitness, nutritional status, and sports participation play important roles in improving learning outcomes in Physical Education, Sports, and Health among elementary school students.